MÍDIA ÉTNICA: UMA ANÁLISE DOS JORNAIS PARA MIGRANTES BRASILEIROS NOS ESTADOS UNIDOS - Neves, Sander Justino (2012)
This is a study on Portuguese language periodicals intended for Brazilians who migrate to the United States. The objective is to map printed periodicals in Massachusetts and to identify if the Brazilian Times newspaper, the oldest to circulate it in the state, facilitates the acculturation and/or the establishment of the people who had changed the Brazilian lands for the northeast of the United States. The methodology involved bibliographical research, in order to base the study with historical and current concepts of citizenship, community and the problems of migration; documentary research; and half-structuralized interviews and analysis of content of the newspaper. The documentary research gathered data from the ethnic periodicals and from the Brazil - United States migratory situation. The analysis of content took 11 editions of the periodical published between 2001 and 2011, and tried to identify and analyze the journalistic subjects prioritized and their approach, to compare the space destined for journalism to that of advertising and to define the profile of the advertisers. The half-structuralized interviews were undertaken with publishers of the periodical and with Brazilian readers who live in the region where the printed edition circulates. It s conclusion was that the Brazilian Times does help to preserve cultural aspects of Brazilian culture as well as facilitating the integration of the immigrants in to the United States way of life. If on one hand its main objective is profit, since it reserves most of the space for advertising, on the other it presents typical ethnic periodical characteristics, such as its emphasis on subjects of interest to the immigrant community (minority). This makes it an opinion former within the Brazilian community in the United States.